2023
DOI: 10.1007/s12020-023-03399-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between TSH and free thyroxine in outpatient cancer patient population

Abstract: BackgroundThe inverse log-linear relationship between Thyroid-stimulating hormone (TSH) and free thyroxine (FT4) is well established and reliably used for evaluation of hypothalamus-pituitary-thyroid (HPT) axis function.However, there are limited data regarding oncologic states in the TSH-FT4 relationship. The purpose of this study was to evaluate thyroid pituitary hypothalamic feedback regulation by the inverse log TSH and FT4 relationship in the cancer patient population at the Ohio State University Comprehe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The results of this large cohort study is likely to be supported by two previously published observational studies conducted by Chen et al, they reported an increased risk and decreased risk of EC in patients with hypothyroidism and hyperthyroidism, although this association was not statistically significant 26 , 27 . Their findings may also be supported by a recently published retrospective study in which an inverse correlation between TSH and FT4 was observed in a cancer patient population and may indirectly explain our findings 28 . Another large cohort study published previously by Kang et al showed inconsistent results that hypothyroidism or hyperthyroidism were not significantly associated with EC or OC risk 29 .…”
Section: Discussionsupporting
confidence: 90%
“…The results of this large cohort study is likely to be supported by two previously published observational studies conducted by Chen et al, they reported an increased risk and decreased risk of EC in patients with hypothyroidism and hyperthyroidism, although this association was not statistically significant 26 , 27 . Their findings may also be supported by a recently published retrospective study in which an inverse correlation between TSH and FT4 was observed in a cancer patient population and may indirectly explain our findings 28 . Another large cohort study published previously by Kang et al showed inconsistent results that hypothyroidism or hyperthyroidism were not significantly associated with EC or OC risk 29 .…”
Section: Discussionsupporting
confidence: 90%
“…2 In clinical practice, the measurement of thyroid-stimulating hormone (TSH), tetraiodothyronine (T4), and triiodothyronine (T3) levels in the blood has been extensively studied in various diseases, including cancer, type 2 diabetes mellitus, non-alcoholic fatty liver disease (NAFLD), and acute-on-chronic liver failure. [3][4][5][6][7] In patients with diabetes and NAFLD, the levels of free triiodothyronine (FT3) and total triiodothyronine (TT3) were found to be significantly higher, while free tetraiodothyronine (FT4) was lower compared to those without NAFLD. 3 Furthermore, levels of FT3 and FT4 were significantly lower in patients with progressive liver fibrosis compared to those without progressive liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%